Reporting reimbursement price decisions for onco-hematology drugs in Spain - Elvira, David; Torres, Ferran; Vives, Roser; Puig, Gemma; Obach, Mercè; Gay, Daniel; Varón, Daniel; de Pando, Thais; Tabernero, Josep; Pontes, Caridad (Frontiers in Public Health, 2023)
Introduction Even using well-established technology assessment processes, the basis of the decisions on drug price and reimbursement are sometimes perceived as poorly informed and sometimes may be seen as disconnected from value. The literature remains inconclusive about how Health Technology Assessment Bodies (HTAb) should report the determinants of their decisions. This study evaluates the relationship between oncology and hematology drug list prices and structured value parameters at the time of reimbursement decision in Spain. Methods The study includes all new onco-hematological products (22), with a first indication authorized between January 2017 and December 2019 in Spain and pricing decisions published up until October 2022. For each product, 56 contextual and non-contextual indicators reflecting the structured multiple criteria decision analysis (MCDA) – Evidence-based Decision-Making (EVIDEM) framework were measured. The relationship between prices and the MCDA-EVIDEM framework was explored using univariate statistical analyses. Results Higher prices were observed when the standard of care included for combinations, if there were references to long-lasting responses, for fixed-duration treatment compared to treatment until progression and treatment with lower frequencies of administration; lower prices were observed for oral administration compared to other routes of administration. Statistically significant associations were observed between prices and the median duration of treatment, the impact on patient autonomy, the ease of use of the drug, and the recommendations of experts. Discussion The study suggests that indicators related to the type of standard of care, references to long-lasting responders, the convenience of the use of the drug, and the impact of treatment on patient autonomy, as well as contextual indicators such as the existence of previous clinical consensus, are factors in setting oncology drug prices in Spain. The implementation of MCDA-EVIDEM methodologies may be useful to capture the influence on pricing decisions of additional factors not included in legislation or consolidated assessment frameworks such as the European Network for Health Technology Assessment (EunetHTA) core model. It may be opportune to consider this in the upcoming revision of the Spanish regulation for health technology assessments and pricing and reimbursement procedures.